Cognitive media theory - Nannicelli, Ted; Taberham, Paul (New York : Routledge, 2014)
'The question of what bearing scientific inquiry has upon the humanities is the subject of an important, ongoing debate in film and media studies. In the latest addition to the AFI Film Readers series, Cognitive Media Theory presents a case that the theorization of film and media spectatorship needs to take current empirical research in the sciences into consideration, and to show how empirical research informs film and media studies. Exploring topics that range from color perception and moral engagement to our cognitive response to humor, Cognitive Media Theory offers film and media scholars and advanced students an introduction to current cognitive theory through original essays that critically reflect upon the current state of the field. Contributors address key topics, genres, and media forms, and present the findings of specific experiments and case studies conducted across film, television, and video games'--
Includes bibliographical references (pages 303-330) and index.
Keywords: Mass media; Humanities -- Research; Social sciences -- Research